2018
DOI: 10.3389/fphar.2018.00249
|View full text |Cite|
|
Sign up to set email alerts
|

Oral Ultramicronized Palmitoylethanolamide: Plasma and Tissue Levels and Spinal Anti-hyperalgesic Effect

Abstract: Palmitoylethanolamide (PEA) is a pleiotropic lipid mediator with established anti-inflammatory and anti-hyperalgesic activity. Ultramicronized PEA (PEA-um) has superior oral efficacy compared to naïve (non-micronized) PEA. The aim of the present study was two-fold: (1) to evaluate whether oral PEA-um has greater absorbability compared to naïve PEA, and its ability to reach peripheral and central tissues under healthy and local inflammatory conditions (carrageenan paw edema); (2) to better characterize the mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
3
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(85 citation statements)
references
References 102 publications
(148 reference statements)
3
78
3
1
Order By: Relevance
“…60 Even if this exogenous administration increases PEA levels in liver of HFD mice, we did not detect any change either of palmitic or palmitoleic or oleic acid content. 60 Even if this exogenous administration increases PEA levels in liver of HFD mice, we did not detect any change either of palmitic or palmitoleic or oleic acid content.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…60 Even if this exogenous administration increases PEA levels in liver of HFD mice, we did not detect any change either of palmitic or palmitoleic or oleic acid content. 60 Even if this exogenous administration increases PEA levels in liver of HFD mice, we did not detect any change either of palmitic or palmitoleic or oleic acid content.…”
Section: Discussioncontrasting
confidence: 55%
“…It has been demonstrated that ultramicronized PEA formulation is promptly absorbed. 60 Even if this exogenous administration increases PEA levels in liver of HFD mice, we did not detect any change either of palmitic or palmitoleic or oleic acid content. In addition, it should be considered that the amount of palmitic acid derived by PEA degradation is negligible respect to whole tissue concentration, which is tightly controlled around a well-defined concentration and depends on exogenous source and endogenous biosynthesis.…”
Section: Discussioncontrasting
confidence: 55%
“…Moreover, in a previous study, we displayed superior efficacy of micronized and ultramicronized PEA formulations matched to PEA that was not micronized (15). The process of micronization is useful to reduce the size of a particle and to improve the bioavailability and effectiveness of particular low-watersoluble molecules increasing the dissolution rate (42)(43)(44).…”
Section: Discussionmentioning
confidence: 73%
“…This smaller size (implying a higher surface-to-volume ratio) along with increased potential energy of the particles leads to better solute solubility. These characteristics result in better diffusion and distribution of micronized and ultramicronized PEA compared to the naïve form, and thus superior biological efficacy [10,12]. The properties of umPEA prompted us to investigate the effect of umPEA ?…”
Section: Introductionmentioning
confidence: 99%